45. E-HEALTH COMPETENCY OF GENERAL NURSING STUDENTS AT PHAM NGOC THACH UNIVERSITY OF MEDICINE (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to assess the eHealth literacy levels of undergraduate nursing students enrolled at Pham Ngoc Thach University of Medicine.Method: A cross-sectional study was conducted among 264 nursing students from first to fourth year. The study utilized a modified Vietnamese version of the eHealth Literacy Scale, consisting of 24 items categorized into five dimensions.Results: The overall median eHealth literacy score was 4.00 (interquartile range: 3.79-4.21), indicating a moderate to high level of competence. The lowest median score was observed in the dimension “seeking and understanding online health information” (3.87), while the highest was in “digital communication and motivation to use health technology” (4.00).Conclusion: Nursing students at Pham Ngoc Thach University of Medicine demonstrated a solid foundation in eHealth literacy, particularly in technology-related and digital communication skills. However, limitations remain in their ability to search for and critically evaluate online health information, suggesting a need for further emphasis in formal training programs.
Keywords: eHealth literacy; nursing students; eHEALS; health technology; Pham Ngoc Thach University of Medicine.